Find the product.
-2x a(-4x b - 2x 3 + 5x)

Question

Asked 10/16/2013 4:37:22 PM

Updated 7/8/2014 11:45:58 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [7/8/2014 11:45:58 AM]

s

andrewpallarca|Points 26529|

andrewpallarca|Points 26529|

andrewpallarca|Points 26529|

lena.G|Points 261|

Question

Asked 10/16/2013 4:37:22 PM

Updated 7/8/2014 11:45:58 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [7/8/2014 11:45:58 AM]

Rating

8

(8m - 4n) + (6m + 3n) = 14m - n

Added 7/8/2014 11:45:23 AM

This answer has been confirmed as correct and helpful.

8

2y^2(3x + 5z)

=(2y^2)(3x)+(2y^2)(5z)

=6xy^2+10y^2z

=(2y^2)(3x)+(2y^2)(5z)

=6xy^2+10y^2z

Added 7/8/2014 11:45:57 AM

This answer has been confirmed as correct and helpful.

2y 2(3x + 5z) **Weegy:** y = 4 - 3x/2 **User:** 2y ^2(3x + 5z) **User:** x 3(x 2 + 5x + 1) **Weegy:** 5x=20, x=20/5, x=4 **User:** x ^3(x ^2 + 5x + 1) **Weegy:** 5x=20, x=20/5, x=4 **User:** Simplify p(p - q) - q(q - p).
**Weegy:** b(a + b) - a(a - b) is equal to n^2-a^2+2ab or -a^2+2ab+b^2. SOLUTION: b(a + b) - a(a - b) ab+b^2-a^2+ab b^2-a^2+ab+ab n^2-a^2+2ab or -a^2+2ab+b^2 **User:** -4x 3 y 2(7xy 4) **Weegy:** The answer is -28x^4y^5 (More)

Question

Updated 5/24/2014 11:17:07 AM

4 Answers/Comments

2y^2(3x + 5z) = 6xy^2 + 10y^2z

Added 5/24/2014 11:14:33 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/24/2014 11:24:42 AM]

x^3(x^2 + 5x + 1) = x^5 + 5x^4 + x^3

Added 5/24/2014 11:15:14 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/24/2014 11:25:55 AM]

p(p - q) - q(q - p)

= p^2 - pq - q^2 + pq

= p^2 - q^2

= p^2 - pq - q^2 + pq

= p^2 - q^2

Added 5/24/2014 11:16:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/24/2014 11:25:50 AM]

Simplify 3j - {2k - [5h - (3j + k)] **Weegy:** : Simplify 3j - {2k - [5h - (3j + k)]}.
answer is -3k+5h **User:** Simplify n - {1 - [n - (1 - n) - 1]}. **Weegy:** Questionnaire and Interviews is a written instrument designed to gather information. **User:** Simplify a - {5b - [a - (3b - 2c) + c - (a - 2b - c)]}. **Weegy:** 3-3 = 0 **User:** Simplify {n - 1 - [n - 1 - (n - 1)]}. **Weegy:** Questionnaire and Interviews is a written instrument designed to gather information. **User:** Simplify (x - y + 1) - (x + y - 1). **User:** Find the product.
-2x a(-4x b - 2x 3 + 5x)
**Weegy:** 2x a(-4x b - 2x 3 5x), The result is 2xa(-4bx-30x^2) (More)

Question

Updated 5/24/2014 11:23:31 AM

2 Answers/Comments

n - {1 - [n - (1 - n) - 1]}

= n - [1 - (n - 1 + n - 1)]

= n - [1 - (2n - 2)]

= n - (1 - 2n + 2)

= n - (3 - 2n)

= n - 3 + 2n

= 3n - 3

= n - [1 - (n - 1 + n - 1)]

= n - [1 - (2n - 2)]

= n - (1 - 2n + 2)

= n - (3 - 2n)

= n - 3 + 2n

= 3n - 3

Added 5/24/2014 11:22:08 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/24/2014 11:29:32 AM]

{n - 1 - [n - 1 - (n - 1)]}

= n - 1 - (n - 1 - n + 1)

= n - 1

= n - 1 - (n - 1 - n + 1)

= n - 1

Added 5/24/2014 11:23:31 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/24/2014 11:32:12 AM]

-4x 3 y 2(7xy 4) **Weegy:** The answer is -28x^4y^5 **User:** Simplify 8y(y - 4) + 3y(y + 2) **User:** - y(2y 3 - 8) **User:** a 4(3a 2 - 2a + 1) **Weegy:** 3-3 = 0 **User:** Take 2y 2 - 3y - 5 from y 3 - 6y 2 + 5y. (More)

Question

Updated 6/5/2014 9:57:12 PM

1 Answer/Comment

Simplify [7m+3n-11-2m]+[n+5- m-3n+8
]

Question

Updated 5/30/2014 9:40:06 AM

1 Answer/Comment

[7m+3n-11-2m]+[n+5- m-3n+8 ]

= (5m + 3n - 11) + (-2n - m + 13)

= 5m + 3n - 11 - 2n - m + 13

= 4m + n + 2

= (5m + 3n - 11) + (-2n - m + 13)

= 5m + 3n - 11 - 2n - m + 13

= 4m + n + 2

Added 5/30/2014 9:40:06 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:42:39 AM]

Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3).
**Weegy:** Simplify -(-2a + 13) + (-9a - 2) - (-7a - 3). -12 **User:** Simplify [7m+3n-11-2m]+[n+5- m-3n+8 (More)

Question

Updated 5/30/2014 9:42:29 AM

1 Answer/Comment

-(-2a + 13) + (-9a - 2) - (-7a - 3)

= 2a - 13 - 9a - 2 + 7a + 3

= (2a - 9a + 7a) + (-13 - 2 + 3)

= - 12

= 2a - 13 - 9a - 2 + 7a + 3

= (2a - 9a + 7a) + (-13 - 2 + 3)

= - 12

Added 5/30/2014 9:42:29 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:45:45 AM]

32,731,590

questions answered

There are no comments.